2019
DOI: 10.1521/aeap.2019.31.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Medical Providers and Harm Reduction Views on Pre-Exposure Prophylaxis for HIV Prevention Among People Who Inject Drugs

Abstract: Despite high pre-exposure prophylaxis (PrEP) acceptability among people who inject drugs (PWID) and PrEP providers, PrEP uptake is low and little is known about how to promote PrEP among PWID. This qualitative study with providers in North Carolina explored views on PrEP delivery approaches for PWID. Interviewers conducted semistructured interviews with 10 PrEP providers and 10 harm reduction (HR) providers. Interviews were transcribed and analyzed. Many participants expressed acceptability for providing PrEP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 19 publications
(19 reference statements)
2
30
0
Order By: Relevance
“…With the vast growth of opioid intervention court programs across the country [ 38 ], incorporating activities connecting infectious disease prevention with current services such as medication-assisted treatment is imperative. Our findings echo those of prior studies regarding a need for informed integration of harm reduction with HIV prevention services [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…With the vast growth of opioid intervention court programs across the country [ 38 ], incorporating activities connecting infectious disease prevention with current services such as medication-assisted treatment is imperative. Our findings echo those of prior studies regarding a need for informed integration of harm reduction with HIV prevention services [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…With the vast growth of opioid intervention court programs across the country (32), incorporating activities connecting infectious disease prevention with current services such as medication-assisted treatment is imperative. Our ndings echo those of prior studies regarding a need for informed integration of harm reduction with HIV prevention services (33,34).…”
Section: Discussionsupporting
confidence: 85%
“…[83][84][85][86]89 Providers also prefer service colocation, which could include placing PrEP providers within an SSP or allowing standing PrEP orders for PWID at SSPs. 73,99 Evidence-based program models for successful PrEP implementation within SSPs remain sorely needed. Two studies found that although most PWID accessing SSPs expressed interest in using PrEP, none initiated PrEP.…”
Section: Role Of Syringe Services Programs In Hiv Testingmentioning
confidence: 99%